Pengaruh Motivasi Kerja dan Kesesuaian Kompetensi Praktik Kerja Lapangan (PKL) terhadap Kesiapan Kerja Siswa SMKN 1 Cinangka - Rizal Amri; Irwanto Irwanto; Didik Aribowo (LPPM Institut Nasional Laa Roiba Bogor, 2022)
This research is a quantitative study which was carried out to measure the independent and dependent variables using numbers that were processed through statistical analysis. This study aims to find out whether there is an influence between 1) The effect of work motivation on the work readiness of SMKN 1 Cinangka students 2) The influence of the suitability of field work practice (PKL) competencies on the work readiness of SMKN 1 Cinangka students 3) the influence of work motivation and the suitability of competencies on readiness SMKN 1 Cinangka students. The method used is the distribution of the instrument on the research sample that has been determined from the population where the research is intended. The results of this study are (1) there is a positive influence of work motivation on the work readiness of SMKN 1 Cinangka students with a correlation value = 0.377 with a significance level of 5% and a contribution of 73.8%. (2) there is a positiv e influence on the suitability of PKL competencies on the work readiness of SMKN 1 Cinangka students with a correlation value = 0.467 with a significance level of 5% and a contribution of 34.1%. (3) there is a positive effect of work motivation and suitability of competencies on the work readiness of SMKN 1 Cinangka students with a correlation value of = 0.558 with a significance level of 5% and a contribution of 61.1%. It can be concluded that there is an influence between work motivation (X1) on work readiness (Y), there is an influence between the suitability of PKL competence (X2) to (Y), there is an influence between work motivation (X1) and the suitability of competence (X2) on work readiness ( Y). Keywords: The Influence of Work Motivation, Competence Suitability of PKL, Work Readiness.